Beyond short-term events. The Mexico-US migration as a long-term phenomenon - Fernández Guzmán, Eduardo (Acta Universitaria, 2013)
In order to understand the scope of the migration phenomenon, it is only reasonable to have a panoramic view and historical knowledge regarding population movements in general and human migrations in particular. Traditional historians have limited their analysis to events or biographies of great personalities, which have occurred in brief moments in history. Beyond the events that move at an accelerated rate are certain realities that are slowly changing. Such is the case of long-term, migration. Situations regarding economic crisis and United States (US) border control have convinced many that we are on the verge of the end of the US-Mexico migration era. It is false. Through historical analysis, this article aims to explain that this phenomenon is still active because conditions of agency, culture and migration traditions, economic disparity and wages, the need for manual cheap labor, among other long-term structures are still valid.
Keywords: Array; Array; Array; Array; Array